Working capital management and financing decision: Synergetic effect on corporate profitability - Solabomi O. Ajibolade; Oboh Collins Sankay (International Journal of Management, Economics and Social Sciences (IJMESS), 2013)
Persuaded by the pecking order assumptions, where internal fund is preferred over debt and equity when financing investment projects, this study provided empirical evidence on the interaction between working capital management and corporate debt structure, and the effect of this on corporate profitability. The assumption on which the study was based is that, if internal funds become the preferred source of finance for investment projects, then working capital composition is interfered, making both decisions co-dependent. A pool of time-series and cross-sectional dataset was constructed from the annual audited financial results of 35 manufacturing companies listed on the Nigerian stock exchange for a two-year period (2011 - 2012). Panel exploration and Factorial-ANOVA estimation techniques were used to estimate the econometric models developed for the study. The results suggested a significant negative relationship between firm's working capital composition and their debt structure choice. Additionally, on individual basis, the study found a positive significant relationship between debt structure and profitability but no significant relationship between firm's working capital composition and profitability. The results, however, showed that as the firm's working capital composition synchronously interacts with the debt structure, corporate profitability is positively affected. The study therefore recommends that, for firms to optimize profitability and to maintain good liquidity position, corporate financing decision should be considered side by side with their working capital composition.
Keywords: O16; E22; G32; 330; Pecking-order assumptions; working capital composition; debt structure choice; profitability